The happy day - Krauss, Ruth (New York : HarperCollins.)
Snow is falling. All the animals are fast asleep in their animals homes. They awake. They open their eyes. They sniff. They run. What will they find?
A Caldecott Honor book
Keywords: Animals -- Fiction; Children stories